2022
DOI: 10.1007/s12144-021-02693-5
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of ADHD and allergic diseases in early adolescence: The role of parental smoking at home

Abstract: A growing body of research suggests an association between attention deficit hyperactivity disorder (ADHD) and allergic disorders, but little work has been done to explore the role of external factors such as parental smoking at home in the development of comorbid ADHD and allergic disorders. This study aimed to examine the association between allergic diseases and ADHD adjusted for exposure to parental smoking at home in early adolescents. We recruited 250 male (41.7%) and 350 female (58.3%) adolescents (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, Annesi-Maesano emphasized that children with behavioral problems are more inclined to develop asthma than other children [7]. On the other hand, several studies have reported an increased prevalence of allergic diseases, including asthma, among patients with ADHD or other psychological-behavioral problems [28][29][30]. Based on this, several scholars have proposed that the relationship between childhood asthma and behavioral problems was a bidirectional [4,27,31] and even cyclical one [27,32], requiring rigorous longitudinal studies and an integrated model incorporating environmental factors, parental mental health, and child psychological problems to provide information on possible mechanisms linking asthma and behavioral problems [15,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Annesi-Maesano emphasized that children with behavioral problems are more inclined to develop asthma than other children [7]. On the other hand, several studies have reported an increased prevalence of allergic diseases, including asthma, among patients with ADHD or other psychological-behavioral problems [28][29][30]. Based on this, several scholars have proposed that the relationship between childhood asthma and behavioral problems was a bidirectional [4,27,31] and even cyclical one [27,32], requiring rigorous longitudinal studies and an integrated model incorporating environmental factors, parental mental health, and child psychological problems to provide information on possible mechanisms linking asthma and behavioral problems [15,27].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IL-6 in the brain has been shown to be associated with symptoms such as impaired cognitive function, learning disabilities and reduced social activity [5]. Another study showed differences in IgE levels that may explain ADHD symptoms in allergic patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Suwan et al [ 6 ] investigated the prevalence of allergic diseases in ADHD children ( n = 40) compared to non-ADHD controls ( n = 40); in this study, they identified a higher number of maternal smoking in ADHD patients (3/40) but without a statistical significance ( p = 0.241) and without specifying if the patients were allergic or not. Second-hand smoke exposure at home was defined as a potential risk factor for developing ADHD and allergic diseases (especially food allergy) in the study of Wong et al [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that ADHD patients are more likely to present with asthma, allergic rhinitis (AR), allergic conjunctivitis, atopic dermatitis, and psoriasis ( Wang et al, 2018a ; Chang et al, 2021 ). Studies also show that various inflammation-associated genes and inflammatory mechanisms play a role in the occurrence of ADHD ( Leffa et al, 2018 ; Wong et al, 2022 ). For example, increased interleukin-6 (IL-6) levels may impact neural pathways, neurogenesis, and synaptic plasticity in the prefrontal cortex and hippocampus of pediatric patients ( Hunter and Jones, 2015 ).…”
Section: Introductionmentioning
confidence: 99%